Blood Pressure-Lowering Mechanisms of the DASH Dietary Pattern. (30th January 2012) - Lin, Pao-Hwa; Allen, Jason D.; Li, Yi-Ju; Yu, Miao; Lien, Lillian F.; Svetkey, Laura P.
Abstract : Potential blood pressure- (BP-) lowering mechanisms of the DASH dietary pattern were measured in 20 unmedicated hypertensive adults in a controlled feeding study. At screening, participants averaged 44.3 ± 7.8 years, BMI 33.9 ± 6.6  Kg/m 2, and BP 144.2 ± 9.38 / 88.5 ± 6.03  mmHg. All consumed a control diet for one week, then were randomized to control or DASH for another two weeks (week one and two). With DASH, but not controls, SBP fell by 10.65 ± 12.89 (P = 0.023 ) and 9.60 ± 11.23 (P = 0.039 ) mmHg and DBP by 5.95 ± 8.01 (P = 0.069 ) and 8.60 ± 9.13  mmHg (P = 0.011 ) at the end of week one and two, respectively. Univariate regressions showed that changes in urinary sodium/potassium ratio (β = 1.99 ) and plasma renin activity (β = − 15.78 ) and percent change in plasma nitrite after hyperemia were associated with SBP changes at week one (all P < 0.05 ). Plasma nitrite following hyperemia showed a treatment effect (P = 0.014 ) and increased at week two (P = 0.001 ). Pulse wave velocity decreased over time with DASH (trend P = 0.019 ), and reached significance at week two (P = 0.026 ). This response may be mediated by an improvement in upregulation of nitric oxide bioavailability. Early natriuresis and reductions in oxidative stress cannot be ruled out. Future studies are needed to verify these findings, assess the possibility of earlier effects, and examine other potential mediators.